2001
DOI: 10.1046/j.1471-4159.2001.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotective agent ebselen modifies NMDA receptor function via the redox modulatory site

Abstract: Ebselen is a seleno-organic compound currently in clinical trials for the treatment of ischemic stroke and subarachnoid hemorrhage. Its putative mode of action as a neuroprotectant is via cyclical reduction and oxidation reactions, in a manner akin to glutathione peroxidase. For this reason, we have investigated the effects of ebselen on the redox-sensitive NMDA receptor. We have found that ebselen readily reversed dithiothreitol (DTT) potentiation of NMDA-mediated currents in cultured neurons and in Chinese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…In fact, diphenyl diselenide reduced about 37% the appearance of seizure episodes induced by glutamate. Although we did not focus on mechanisms by which diphenyl diselenide was capable of protecting seizures induced by glutamate, our results are in accordance with previous data reported by us [2] and others [36]. In fact, diphenyl diselenide produced pharmacological effect in several models of pain through mechanisms that involve an interaction with redox modulatory sites of glutamate receptors [2].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, diphenyl diselenide reduced about 37% the appearance of seizure episodes induced by glutamate. Although we did not focus on mechanisms by which diphenyl diselenide was capable of protecting seizures induced by glutamate, our results are in accordance with previous data reported by us [2] and others [36]. In fact, diphenyl diselenide produced pharmacological effect in several models of pain through mechanisms that involve an interaction with redox modulatory sites of glutamate receptors [2].…”
Section: Discussionsupporting
confidence: 91%
“…3). An analogous study has shown that ethanol inhibits LTP formation by blocking the NMDA receptor, possibly because the cysteine residues of NR2B are sensitive to ethanol (Herin et al 2001), and leads to amnesia (Brioni et al 1989;Dildy and Leslie 1989;Tokuda et al 2007;Wirkner et al 1999). Some studies have shown that formaldehyde can spontaneously modify the cysteine residues of proteins (Metz et al 2006;Toews et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6), resulting in a change of the channel gating properties. Site-directed mutagenesis identified Cys399 as the critical cysteine ( Table 1) targeted by endogenous nitrogen species and various redox modulators, including reducing and oxidizing agents (Tang and Aizenman, 1993;Kim et al, 1999;Sanchez et al, 2000;Herin et al, 2001). They all modify the NMDA receptor at this specific cysteine (Lipton et al, 1993;Choi et al, 2000) and thereby modify glutamateevoked calcium fluxes through the channel.…”
Section: B Redox Modulation Of Glutamate Signaling In Nociceptive Pamentioning
confidence: 99%